Sexual Abuse An Interdisciplinary Approach - Kalfoğlu, Ersi; Kalfoglou, Sotirios (IntechOpen, 2022)
Sexual assaults are special crimes that require an inter-multidisciplinary approach. This book brings together the work of distinguished scientists on sex crimes and their prevention. It is organized into two sections on the behavioral aspects of sexual abuse/assault and the methods of responding to these types of cases. Chapters address such topics as child abuse, dating violence in the online era, marital rape, and much more.